Effect of stoichiometry on chemical structure, dielectric and mechanical properties of epoxy resin under gamma irradiation. (January 2023) - Liu, Wen; Huang, Wei; Song, Ningning; Wu, Yeping; Zhao, Xiuli; Chen, Keping
Abstract: The chemical and physical properties of diglycidyl ethers of bisphenol-A (DGEBA)/2, 2'-(ethylenedioxy) bis(ethylamine) (EDBA) epoxy resins with different stoichiometric ratios under gamma irradiation have been investigated. Fourier transform infrared (FTIR) spectroscopy results indicated that a mass of amines and oxidized carbonyl-containing products were generated during the irradiation process. Most products for amine-rich DGEBA/EDBA systems were amides. Dynamic mechanical analysis (DMA) and differential scanning calorimetry (DSC) results demonstrated that chain scission predominated during irradiation for the amine-rich system, while chain cross-linking predominated for the epoxy-rich system. The dielectric relaxation behaviours indicated that the α relaxation behaviours broadened considerably with an increasing irradiation dose, demonstrating an increasing spatial heterogeneity of the crosslinked networks. The compressive yield strengths showed a monotonous linear increase with irradiation dose. However, due to the different cross-linking networks, the yield strains showed converse trends for amine-rich and epoxy-rich systems under gamma irradiation. Highlights: Stoichiometry has great impact on chemical and physical properties of epoxy resins. An increasingly spatial heterogeneity of the cross-linking networks was observed. Chain scission predominated during irradiation for amine-rich system. Chain cross-linking predominated during irradiation for epoxy-rich system. The yield strains showed converse tendency for amine-rich and epoxy-rich systems.